The journal of James Edmond Pease : a Civil War Union soldier - Murphy, Jim, 1947-; local (New York : Scholastic, 2003)
James Edmond, a sixteen-year-old orphan, keeps a journal of his experiences and those of "G" Company which he joined as a volunteer in the Union Army during the Civi
"Virginia, 1863"--Cover.
l War.
Follett Library Resources
Keywords: 5-8; sears -- United States -- History -- Civil War, 1861-1865; Fiction. -- Orphans; Fiction. -- Diaries; Fiction; Historical fiction. -- United States -- History -- 1861-1865, Civil War; sears -- Orphans; sears -- Diaries; sears